Design of salt-bridge cyclization peptide tags for stability and activity enhancement of enzymes. (June 2019) - Tang, Lingjun; Yang, Ji; Chen, Jie; Zhang, Jing; Yu, Huimin; Shen, Zhongyao
Graphical abstract: Highlights: Salt-bridge cyclization peptide tag (SbCPT) was used to modify the enzyme terminus. The extensible enzyme terminus would be a favorable spot to attach the SbCPT. GRPDG was analyzed as an optimal SbCPT to ameliorate enzyme properties. The stability of SbCPT-attached NHase improved by 32.7% with non-reduced activity. The introduction of GRPDG also enhanced the thermal stability of nitrilase by 30.3%. Abstract: The terminus is usually the most flexible and fluctuating part that affects the enzyme stability. In this study, we proposed an enzyme terminus stabilization strategy based on the attachment of a salt-bridge cyclization peptide tag (SbCPT) without activity loss. SbCPTs of different lengths, as well as different subunit termini of nitrile hydratases from Rhodococcus ruber TH (NHase M -TH) for SbCPT insertion, were investigated by molecular dynamics (MD) simulations and mutagenesis experiments. The investigation revealed that a smaller SbCPT would be favorable and that the SbCPT should only be attached on the enzyme terminus that is extensible and also far from any special functional area due to the minimal influences on the enzyme structure. The stability of different SbCPTs types (GK PE G, GK PD G, GR PE G, GR PD G) was identified as RD > RE > KD > KE. By insertion of an optimal SbCPT (GRPDG) to the C-terminus of the α-subunit of NHase, the SbCPT-attached NHase variants demonstrated improved stability by a maximum of 32.7%, as well as the overall catalytic competence. Additionally, the effect of SbCPT with enhanced stability and non-reduced activity was also verified in nitrilase from Rhodococcus rhodochrous tg1-A6, indicating a general applicability of the convenient SbCPT strategy for better industrial applications.